DISTRIBUSI SUSPENSI DAN SEDIMEN DI TELUK JAKARTA DAN PERAIRAN KEPULAUAN SERIBU - Helfinalis Helfinalis (Universitas Gadjah Mada, 2005)
The objectives of this study were to know total suspended solid (TSS) and sediment distributions in Jakarta bay and Seribu Islands waters. This study was conducted on 5-11 August 2003. Water samples for TSS measurement were taken from the water surface (2 m depth), 1 m upper the bottom surface, and in the middle of water column in each station. The highest TSS was found at 0.75 g/l on the water surface in front of the westside of Cengkareng drain. In Seribu Island waters, TSS was lower than 0.07 g/l. High TSS in the middle of water column were found in the north of Untung Jawa Island, Rambut Island waters, and north of Cengkareng drain. The highest TSS in the middle of water column reached 0.0324 g/l in surrounding Muara Angke waters. On the other hand, low TSSs in the middle of water column were found in the east of Untung Jawa Island and in the west of Rambut Island at around 0.0268 g/l. On the bottom, high TSSs were found in the most east of Bidadari and Karang Ubi Islands at 0.23 g/l. Low TSSs at around 0.02 g/l were found in the east and southeast of Untung Jawa Island and the north part of sampling location in this study. Silty mud sediment was observed in the northwest of Cengkareng drain estuary. In the surrounding Dadap and Kamal estuaries, silt, sandy silt, sand, and silty sand sediments were gradually found. Distribution of muddy sand sediment was found very narrow in the Jakarta Bay, but wider in the north of Tanjung Pasir. Silty sand, sand, sandy silt, and silt sediment were observed in the north part of sampling location in this study.The objectives of this study were to know total suspended solid (TSS) and sediment distributions in Jakarta bay and Seribu Islands waters. This study was conducted on 5-11 August 2003. Water samples for TSS measurement were taken from the water surface (2 m depth), 1 m upper the bottom surface, and in the middle of water column in each station. The highest TSS was found at 0.75 g/l on the water surface in front of the westside of Cengkareng drain. In Seribu Island waters, TSS was lower than 0.07 g/l. High TSS in the middle of water column were found in the north of Untung Jawa Island, Rambut Island waters, and north of Cengkareng drain. The highest TSS in the middle of water column reached 0.0324 g/l in surrounding Muara Angke waters. On the other hand, low TSSs in the middle of water column were found in the east of Untung Jawa Island and in the west of Rambut Island at around 0.0268 g/l. On the bottom, high TSSs were found in the most east of Bidadari and Karang Ubi Islands at 0.23 g/l. Low TSSs at around 0.02 g/l were found in the east and southeast of Untung Jawa Island and the north part of sampling location in this study. Silty mud sediment was observed in the northwest of Cengkareng drain estuary. In the surrounding Dadap and Kamal estuaries, silt, sandy silt, sand, and silty sand sediments were gradually found. Distribution of muddy sand sediment was found very narrow in the Jakarta Bay, but wider in the north of Tanjung Pasir. Silty sand, sand, sandy silt, and silt sediment were observed in the north part of sampling location in this study.